Arctic Cyclones and Their Interactions With the Declining Sea Ice: A Recent Climatology. Issue 12 (17th June 2021) - Valkonen, E.; Cassano, J.; Cassano, E.
Abstract: In this study, we applied a cyclone tracking algorithm to multiple reanalyses and categorized the detected cyclones based on season, intensity, and sea ice state to provide an Arctic cyclone climatology with emphasis on cyclone‐sea ice interactions over the Arctic Ocean and adjacent waters. Our study period is from 1979 to 2015 and the reanalyses we are using are ERA‐Interim, ERA5, and CFSR. As for our intensity variable, we use Accumulated Cyclone Energy (ACE), which has commonly been used as an intensity metric in the tropics but has not been utilized for high latitudes before. ACE has the advantage that it relates the cyclone intensity to the kinetic energy of the cyclone and therefore better represents the cyclone impact/interaction with the surface. We performed comparisons with the other more commonly used intensity metrics to assess the use of the ACE metric in the Arctic. Our main findings include increased cyclone counts with higher trends toward the end of the study period. Cold season cyclone counts were also found to be related to decreased sea ice concentration throughout the year. We also show that there is a relationship between the cyclone intensity measured by ACE and the surface state. Less sea ice was shown to be related to higher cyclone intensities. Comparisons between the the three reanalysis data sets are also presented. Plain Language Summary: In this study, three cyclone data sets were compared over the Arctic Ocean and adjacent waters to have a better understanding of how Arctic storms interact with the sea ice. Our study period is from 1979 to 2015, and we assessed multiple different storm characteristics, such as the size and intensity of the storm, to study the storms' relationships with the sea ice. We found that in the cold season (December–May), less sea ice was related to more and stronger cyclones, and that the amount of sea ice present had an influence on the cyclone strength over the study region. Key Points: Less sea ice is related to higher cyclone track counts Less sea ice is related to stronger cyclones The new ERA5 reanalysis detects smaller cyclones than the ERA‐Interim or CFSR data sets